Pandangan Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Airlangga Tentang Kepatuhan Syariah di Bank Syariah - Usnah, Siti Asmaul; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Sharia compliance is the main pillar that distinguishes between Islamic banks andÂ conventional banks. Nevertheless, there is still debate among people who use the services ofÂ Islamic banking about sharia compliance regarding to the principles of sharia. This researchÂ aimed to investigate the customerâs perception of Islamic bank in the scope of EconomicÂ and Business Faculty Airlangga University students regarding to sharia compliance practice inÂ Islamic bank which is seen from the concept and indicators of sharia compliance.This research used qualitative approach with a case study. Data collection technique inÂ this research used a Focus Group Discussion (FGD) that consist of four group students of theÂ Economic and Business Faculty Airlangga University from four majors: Economics,Â Management, Accounting, and Islamic Economics. This research was analyzed using domainÂ and componential analysis.The result of this research showed that sharia compliance concept in Islamic bank that has been agreed by all of four student groups of Economic And Business Faculty of AirlanggaÂ University was sharia principles practice in Islamic bank operational system. There were fourÂ indicators of sharia compliance which had been agreed by all of four group students of Economic And Business Faculty of Airlangga University. They were akad as according toÂ sharia, corporate culture as according to sharia, lending scheme as according to sharia,Â halal source of funds. Whereas the indicators which werenât agreed yet by all of four groupstudents of Economic And Business Faculty of Airlangga University were the existence ofÂ Sharia Supervisory Board , financial statements which were reported as according to shariaÂ accounting, and zakat funds.